Effect of Exogenous General Plant Growth Regulators on the Growth of the Duckweed Lemna minor - Utami, Desi; Kawahata, Ami; Sugawara, Masayuki; Jog, Rahul N.; Miwa, Kyoko; Morikawa, Masaaki (Frontiers in Chemistry, 2018)
Gibberellic acid (GA3), indole-3-acetic acid (IAA), salicylic acid (SA), 1-aminocyclopropane-1-carboxylic acid (ACC) and aminoethoxyvinylglycine (AVG) are popular endogenous growth regulators of plants. However, the effects of their exogenous addition on the biomass production of aquatic plants, including Lemnoidae plants, “duckweeds,” are largely unknown. In this study, the growth of Lemna minor was tested for 10 d in Hoagland medium containing each compound at different concentrations of 0−50 µM. GA3, IAA, and SA were found to have no apparent positive effect on the growth at all concentrations tested. Conversely, ACC moderately and AVG severely inhibited the growth of L. minor. Among the tested compounds, ascorbic acid had an apparent growth-promoting effect.